Comparative genomics of a polyvalent escherichia-salmonella phage fp01 and in silico analysis of Its receptor binding protein and conserved enterobacteriaceae phage receptor - Vásquez, Ignacio; Retamales, Julio; Parra, Barbara; Machimbirike, Vimbai; Robeson, James; Santander, Javier (MDPI, 2023)
The polyvalent bacteriophage fp01, isolated from wastewater in Valparaiso, Chile, was described to have lytic activity across bacterial species, including Escherichia coli and Salmonella enterica serovars. Due to its polyvalent nature, the bacteriophage fp01 has potential applications in the biomedical, food and agricultural industries. Also, fundamental aspects of polyvalent bacteriophage biology are unknown. In this study, we sequenced and described the complete genome of the polyvalent phage fp01 (MH745368.2) using long- (MinION, Nanopore) and short-reads (MiSeq, Illumina) sequencing. The bacteriophage fp01 genome has 109,515 bp, double-stranded DNA with an average G+C content of 39%, and 158 coding sequences (CDSs). Phage fp01 has genes with high similarity to Escherichia coli, Salmonella enterica, and Shigella sp. phages. Phylogenetic analyses indicated that the phage fp01 is a new Tequintavirus fp01 specie. Receptor binding protein gp108 was identified as potentially responsible for fp01 polyvalent characteristics, which binds to conserved amino acid regions of the FhuA receptor of Enterobacteriaceae.
Keywords: Polyvalent bacteriophage fp01; Escherichia coli; Genomas; Salmonella